Exponential Stability Analysis of Difference Equation for Impulsive System - S., Elizabeth; S., Nirmal Veena (Journal of Informatics and Mathematical Sciences, 2017)
In this paper, we study the exponential stability of impulsive difference equations with exponential decay and the uniformity of the stability is obtained by using Lyapunov functions. Theorems on exponential and uniform exponential stability are obtained, which shows that certain impulsive perturbations may make unstable systems exponentially stable.